VD_FINDINFO Décision / 2012 / 873 vom 22. Oktober 2012 - VD Tribunal cantonal (2012)
OPPOSITION TARDIVE, RESTITUTION DU DÉLAI, COMPÉTENCE RATIONE MATERIAE, NULLITÉ | 354 CPP (CH), 393 al. 1 let. b CPP (CH), 94 CPP (CH)